PENGARUH HARGA, KUALITAS PRODUK, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KECAP MERK WOWIN - Sanjaya, Mahendra Ega (Universitas Nusantara PGRI Kediri, 2023)
This research was conducted because there were problems in purchasing decisions caused by problems that existed within the company, where problems were in price, product quality, and promotion by the MOWIN Brand Soy Sauce. The purpose of this study was to analyze the effect of price, product quality, and promotions partially and simultaneously on purchasing decisions of MOWIN Brand Soy Sauce. The approach used is a quantitative causality approach. The number of respondents in this study was 40 consumers. The method used is multiple linear regression analysis processed with the help of the SPSS version 23 application. The results of this study indicate a positive effect on the price variable. However, product quality and promotion do not have a positive effect on purchasing decisions. Price, product quality, and promotion have a simultaneous effect on purchasing decisions. It is expected that MOWIN brand soy sauce will pay more attention to price, product quality, and promotions in order to improve sales decisions.